Customer Satisfaction Level of Pharmaceutical Care at Mulawarman Mitra Medika Pharmacy - Boli Matius Tandi Payung; Ratno Adrianto (Mulawarman International Conference on Tropical Public Health, 2025)
Background : A pharmacy is one of the facilities for carrying out pharmaceutical work and distributing pharmaceutical supplies to the public, aimed at improving community health. One of the indicators used to assess the quality of health services is customer satisfaction measurement. Satisfaction refers to the level of a person’s feelings when comparing perceived performance or results with their expectations. Objective : This study aimed to determine the level of patient satisfaction with pharmaceutical services at Apotek Mulawarman Mitra Medika. Research Methods/ Implementation Methods : The research was descriptive and used a satisfaction questionnaire. The subjects were patients who visited Apotek Mulawarman Mitra during a one-month period. Results : Based on the reliability dimension, the majority of respondents (29 people or 58.0%) stated that the service was of good quality, while 21 respondents (42.0%) considered it not good. For the responsiveness aspect, 27 respondents (52.0%) stated that the service was good, and 23 respondents (46.0%) stated otherwise. Regarding assurance, 26 respondents (52.0%) rated the service as good, while 24 respondents (48.0%) did not. Similarly, in the empathy dimension, 26 respondents (52.0%) stated that the service was of good quality, while 24 respondents (48.0%) stated it was not. For the tangible dimension, 26 respondents (52.0%) stated that the service was good, and 24 respondents (48.0%) stated it was not. Overall, the findings indicate that pharmaceutical services at Apotek Mulawarman Mitra Medika are considered to have achieved a satisfactory level of quality across all assessed dimensions. Conclusion/Lesson Learned :